Relationship Between Platelet Distribution Width and the Number of Coronary Artery Lesions in Patients with Acute Coronary Syndrome - Citra Ulina Sitorus; Rahmad Isnanta; Naomi Niari Dalimunthe (Journal of Society Medicine, 2026)
Introduction: Acute coronary syndrome (ACS) results from atherosclerotic plaque and thrombosis, with inflammation and platelet activation involved. Platelet distribution width (PDW), a marker of platelet activation, may reflect involvement. Study evaluated association with diseased vessels in ACS. Methods: This cross-sectional study with retrospective data collection analyzed 111 patients admitted with ACS to H. Adam Malik General Hospital, Medan, between January and December 2024. Demographic, laboratory, and coronary angiographic data were retrieved from medical records. Patients were classified as having single-vessel or multi-vessel disease. Comparisons used the chi-square or Fisher exact test, the independent t-test, and the Mann–Whitney U test as appropriate; a receiver operating characteristic (ROC) curve was constructed to derive the optimal PDW cut-off. Analyses were performed in SPSS version 29, with significance set at p < 0.05. Results: Of the 111 patients, 47 (42.3%) had single-vessel disease and 64 (57.7%) had multi-vessel disease. PDW was significantly higher in the multi-vessel disease group (median 11.0 vs. 10.7 fL; p = 0.002). ROC analysis yielded an area under the curve of 0.68 (95% CI 0.57–0.78) at a PDW cut-off of 10.25 fL, with a sensitivity of 95% and a specificity of 43%. A PDW ≥ 10.25 fL was significantly associated with multi-vessel involvement (p = 0.001). Conclusion: PDW was associated with the number of diseased coronary vessels in patients with ACS. As an inexpensive routine blood count parameter, PDW may serve as an adjunctive marker of coronary lesion complexity; however, modest specificity limits its use as a stand-alone diagnostic tool.